2018
DOI: 10.1111/josi.12282
|View full text |Cite
|
Sign up to set email alerts
|

Everybody but Me: Pluralistic Ignorance and the Masculinity Contest

Abstract: The masculinity contest is a set of organizational norms that fosters competition, work devotion, strength, and dominance. Here, we explore pluralistic ignorance as a mechanism by which these norms persist. Pluralistic ignorance occurs when individuals privately reject a norm, but mistakenly believe others endorse it. This then discourages individuals from criticizing norms that perpetuate unpopular behavioral standards. Drawing on data from U.S. workers, we find masculinity contest norms are prone to pluralis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Munsch et al. () showed that the negative consequences of MCCs may be heightened for those who see MCC norms as incompatible with their own ideals about how organizations should function, but who believe (falsely) that their coworkers view MCC norms as ideal (a form of pluralistic ignorance). Specifically, Munsch et al.…”
Section: In Organizationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Munsch et al. () showed that the negative consequences of MCCs may be heightened for those who see MCC norms as incompatible with their own ideals about how organizations should function, but who believe (falsely) that their coworkers view MCC norms as ideal (a form of pluralistic ignorance). Specifically, Munsch et al.…”
Section: In Organizationsmentioning
confidence: 99%
“…In their survey of U.S. workers, Munsch et al. () found that few respondents personally endorsed masculinity contest norms as an “ideal work environment,” but often believed that coworkers subscribed to these norms. In other words, respondents falsely believed that coworkers approve MCC norms, creating a situation likely to foster MCC norms’ persistence.…”
Section: In Organizationsmentioning
confidence: 99%
See 3 more Smart Citations